2017
DOI: 10.4236/abb.2017.812034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grapefruit Juice on Aluminum-Induced Hepatotoxicity in Albino Rats: Histological, Ultrastructural and Histochemical Assessment

Abstract: The present work studied the effect of grapefruit juice (Citrus) on the hepatotoxicity of AlCl 3 . Four groups of adult male albino rats were used. Group I contained 10 rats and remained as a control group; Group II: 10 rats were included and orally administered with grapefruit juice at a dose level of 27 ml/kg of body weight per day for 6 weeks; Group III: 10 rats were included and AlCl 3 was administered orally at a dose level of 100 mg/kg of body weight per day for 6 weeks; Group IV: animals of this group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The free radicals switched on the unsaturated lipid membrane peroxidation, induced serious destruction of the hepatic cell membrane and structure of organelles, and caused hepatic cell injury, degeneration, necrosis, and liver fibrosis formation induced by a long-term repeated stimulus. Animals treated with grape juice showed a reduced level of AST and ALT enzymes that support the liver structure 8 . Grape juice is rich in antioxidative polyphenols that are the first line of defense against damage by free radicals 12,21 ; the antioxidative activity of grape juice can be attributed to the presence of polyphenols.…”
Section: L-mentioning
confidence: 68%
See 1 more Smart Citation
“…The free radicals switched on the unsaturated lipid membrane peroxidation, induced serious destruction of the hepatic cell membrane and structure of organelles, and caused hepatic cell injury, degeneration, necrosis, and liver fibrosis formation induced by a long-term repeated stimulus. Animals treated with grape juice showed a reduced level of AST and ALT enzymes that support the liver structure 8 . Grape juice is rich in antioxidative polyphenols that are the first line of defense against damage by free radicals 12,21 ; the antioxidative activity of grape juice can be attributed to the presence of polyphenols.…”
Section: L-mentioning
confidence: 68%
“…The grape (Vitis vinifera) is one of the most widely planted fruits, and it shown to contain a variety of nutrients and biologically active substances such as fiber, vitamin C, phenolic compounds including flavonoids, polyphenols, anthocyanins, and minerals such as iron, potassium, zinc, manganese, and calcium (6,7) that reduce oxidative damage. Although grape skin and seeds contain the majority of these beneficial components, grape skin and seeds are wasted annually from the daily diet, while most of the bioactive components with the significant antioxidant and free radical scavenging activity can be found in these wastes (8) . Studies have shown that consuming grape juice improves the lining of blood vessels, reduces platelet aggregation, increases antioxidants activity including DNA oxidative damage, oxidation of low-density lipoprotein, and oxidative damage to the brain (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Group III (MTZ þ GP): received MTZ (400 mg/kg) plus GP juice (27 ml/kg). 16 4. Group IV (GP group): received GP juice (27 ml/kg).…”
Section: Experimental Designmentioning
confidence: 99%
“…In urban areas water is usually treated with aluminum. Aluminum is found in spinach, potatoes, tea, antacids and baking powder 1,2 . In developing countries aluminum utensils are widely used 3 .…”
Section: Introductionmentioning
confidence: 99%